Soft tissue telangiectatic osteosarcoma in a young patient: Imaging and immunostains - Vorachai Sirikulchayanonta (2018)
Telangiectatic osteosarcoma of the soft tissue is rare and generally affects adults older than 50 years of age. We present the case of a 17-year-old male who developed a mass in the right thigh. The CT and MRI findings suggested a malignant hemorrhagic tumor without discernable osteoid matrix. Differential diagnosis included various hemorrhagic mesenchymal tumors. Histology revealed large multiple cysts lined with septae and filled with numerous giant cells, pleomorphic spindle cells, and occasionally an osteoid-like substance. Immunostaining for osteocalcin was positive in the cytoplasm of both stromal mononucleate and multinucleate giant cells. Surgery and adjuvant chemotherapy were applied and the patient survives to the time of writing after 30 months of follow-up without recurrence or metastasis. © ISS 2004.